Oral mucositis in children with cancer: difficulties of evaluation and effective therapy (Research, Society and Development, 2021)
Cancer is a public health problem in the world and, in children, the incidence of increase is around 1% per year. Despite its effectiveness, antineoplastic therapy causes effects of significant toxicity, often causing the patient to be hospitalized, difficult to continue with oncotherapy or not readjusted to the treatment for the non-progression of the disease. Oral mucositis is one of the most common deleterious effects; it causes pain, affects speech and nutrition, and makes the patient susceptible to sepsis. In children, the frequency of oral mucositis is around 65%. Its manifestations are evaluated using different scales and treated with different protocols. The objective of this work is to verify, in a systematic literature review, the state of the art in the evaluation of oral mucositis in children undergoing cancer treatment. Studies have shown that assessment is essential to establish treatment strategies, that protocols and scales used are inconsistent, and that there is no viable and valid system to score childhood mucositis caused by cancer, preventing a more effective therapeutic intervention. It was concluded that the Children's International Mucositis Evaluation Scale has been the scale with the greatest acceptability and validity according to its criteria.